2020
DOI: 10.3390/ijms21020535
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Chitosan Increases Tomato Growth and Influences Mycorrhization and Expression of Endochitinase-Encoding Genes

Abstract: Nowadays, applying bio-organic fertilizer (e.g., chitosan, Ch) or integrating beneficial microorganisms (e.g., arbuscular mycorrhizal fungi, AMF) are among the successful strategies to promote plant growth. Here, the effect of two application modes of Ch (foliar spray or root treatment) and Ch-derived nanoparticles (NPs) on tomato plants colonized with the AMF Rhizophagus irregularis were analyzed, thereby focusing on plant biomass, flowering and mycorrhization. An increase of shoot biomass and flower number w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…Previous studies have demonstrated how CNC can be used without harmful effects on tomato plants, suggesting their potential use as nanocarriers [ 53 ]. Furthermore, chitosan effects on plant vegetative growth are positive when applied on leaves [ 20 , 26 , 31 ]. Our work strongly confirms this response, indicating in both formulation of CH-CNC-Starch NMP the capability of evenly covering tomato leaves without any detrimental side effects on basal vegetative parameters ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated how CNC can be used without harmful effects on tomato plants, suggesting their potential use as nanocarriers [ 53 ]. Furthermore, chitosan effects on plant vegetative growth are positive when applied on leaves [ 20 , 26 , 31 ]. Our work strongly confirms this response, indicating in both formulation of CH-CNC-Starch NMP the capability of evenly covering tomato leaves without any detrimental side effects on basal vegetative parameters ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the application of chitosan is being pursued due to its economic convenience, since it can be obtained from agroindustrial wastes, like seafood shells, which currently represent, unlike the aforementioned substances, a very affordable starting point in defining innovative crop protection compounds [27,28]. Several scientific publications highlight the promising use of chitosan in tomato fungal (Fusarium wilt) and bacterial (bacterial spot and wilt) diseases management, showing good effects on vegetative parameters of plants [29][30][31][32]. Mansilla et al (2013) demonstrated antimicrobial properties of chitosan on Pst, suggesting that inhibition could depend on several chemical parameters (pH, presence of metal ions, concentration), while the mode of action could be related to cell membrane interaction [33].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial activities of chitosan are mostly associated with increased photosynthetic activity, tolerance to abiotic stressors such as drought, salinity and extreme temperatures, as well as with increased antioxidant enzymes activity and the expression of defensive genes [80]. There are numerous examples of chitosan application on vegetable crops; however, the obtained results are not always consistent since the various studies differ in their methodological approach (time and dose of application), while chitosanbased biostimulant products may also differ in chemical composition and chitosan content, which further increases heterogeneity in biological effects [77,78,[81][82][83]. The primary use of chitosan in agriculture is based on its eliciting effects on the biosynthesis of protective biomolecules against pests and pathogens [14,84,85], as well as on the up-regulation of defensive genes [86,87].…”
Section: Practical Applications Of Chitosan On Vegetable Cropsmentioning
confidence: 99%
“…Moreover, chitosan application may result in plant growth improvement mostly through the increased nitrogen and nutrients uptake, while it can be used as an extra carbon source in plant biosynthetic processes [82,92]. Other activities include the effects of mycorrhization in tomato plants through the regulation of the expression of endochitinase-encoding genes [81]. Moreover, the foliar application of chitosan may serve as a physical barrier against pathogens [93], while it can increase the thickness of cell walls in the leaves' epidermis, contributing to tolerance against pathogens attacks [94].…”
Section: Practical Applications Of Chitosan On Vegetable Cropsmentioning
confidence: 99%
“…In agriculture, chitosan has been used to induce plant resistance (Coutinho et al, 2020), increasing the antagonistic capacity of beneficial microorganisms (El Amerany et al, 2020) and crop productivity (Rahman et al, 2018). In phytopathogen control, chitosan induces morphological changes and structural alterations in fungal cells that cause cell death (Berger et al, 2016).…”
Section: Academicpresmentioning
confidence: 99%